2019
DOI: 10.3389/fcimb.2019.00092
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal and Urinary Microbiomes in Premenopausal Women With Interstitial Cystitis/Bladder Pain Syndrome as Compared to Unaffected Controls: A Pilot Cross-Sectional Study

Abstract: Interstitial cystitis/bladder pain syndrome (ICBPS) may be related to an altered genitourinary microbiome. Our aim was to compare the vaginal and urinary microbiomes between premenopausal women with ICBPS and unaffected controls. This cross-sectional study screened premenopausal women with an O'Leary-Sant questionnaire (ICBPS if score ≥6 on either index; controls <6 on both). Women completed questionnaires on health characteristics, pelvic floor symptoms (OABq, PFDI-20), body image (mBIS), and sexual function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
1
40
0
2
Order By: Relevance
“…Currently, there is debate as to whether the vaginal and urinary tract communities are distinct microbiota or if they are interconnected. 16S rRNA gene sequence studies have identified the same genera across the two sites [2,3]. Whole genome sequencing of vaginal and urinary tract isolates of the same species from the same individual suggests that the two microbiota are connected [4].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is debate as to whether the vaginal and urinary tract communities are distinct microbiota or if they are interconnected. 16S rRNA gene sequence studies have identified the same genera across the two sites [2,3]. Whole genome sequencing of vaginal and urinary tract isolates of the same species from the same individual suggests that the two microbiota are connected [4].…”
Section: Plos Onementioning
confidence: 99%
“…Lactobacilli are a prominent member of the healthy female urogenital tract [1]. 16S rRNA gene sequencing and shotgun whole genome sequencing of the vaginal and urinary tract microbiota have identified the same species in both niches, suggesting that the two microbiota are in fact interconnected [2][3][4]. The healthy vaginal microbiota is often dominated by one of four Lactobacillus species: Lactobacillus crispatus, L. iners, L. gasseri, or L. jensenii [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In women, a single, small study of catheterized urine samples revealed decreased bacterial diversity, with reduced Lactobacillus levels and increased proinflammatory cytokines in IC/BPS compared with controls [22•]. Three studies examining voided urine samples in women with IC/BPS were unable to identify differences in individual taxa between control subjects and IC/BPS participants [55][56][57], but did observe trends towards differential abundances of several species, such as increased L. gasseri and lower Corynebacterium prevalence in IC/BPS patients. Earlier studies using both voided and catheterized specimens are similar, visualizing overall changes in diversity without unique disease-associated species.…”
Section: Genitourinary Pain (Ic/bps and Cp/cpps)-for Genitourinary Pamentioning
confidence: 99%
“…Therefore it was very interesting to read this study combining the analysis of the urinary and vaginal microbiome (Meriwether et al, 2019). During enrollment patients were thoroughly screened for interfering conditions such as menopausal status, pelvic organ prolapse beyond the hymen, foreign bodies in the vagina, active urinary or genital tract infection and current treatment for ICBPS.…”
Section: Introductionmentioning
confidence: 99%